Assessing Water Quality Indices and Autopurification Capacity of Balighli-Chai and Ghare-Sou Rivers using QUAL2Kw Model - Gholamreza Rafiee; Fateh Moezzi; Hadi Poorbagher; Kamran Rezaei Tavabe; Mohammad Ali Nematollahi (محیط زیست و مهندسی آب, 2023)
The present study was conducted to assess the water quality of the Balighli-Chai and Ghare-Sou Rivers, the main rivers of Ardabil Province, Iran. The levels of dissolved oxygen (DO), biochemical oxygen demand (BOD), nitrate (NO3) and phosphate (PO4) were measured and simulated using the QUAL2Kw model during low- and high-water periods. Also, self-purification capacity and total maximum daily load (TMDL) levels of water quality parameters were calculated. The obtained results indicated considerable differences between the levels simulated by the model from the measured data for both rivers. Most of the river sections had low self-purification capacities. Maximum self-purification capacity (%) were: high water period: DO = -226.61; BOD5 = 90/30; NO3 = 99.88; PO4 = 96.49; low water period: DO = -281.71; BOD5 = 89.13; NO3 = 94.74; PO4 = 90.21. TMDL scores for DO, BOD5 and NO3 were higher during the high-water period, but entire sections of both rivers showed high excess loads of PO4. The results showed that most ranges of both rivers didn't have appropriate water quality conditions. Therefore, it is necessary to make proper decisions to control pollution levels and improve water quality in this basin